Marine communication for shipping: Using ad-hoc networks at sea - Neermegha Mishra; Marvin Kastner; Carlos Jahn (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Oceans are a dominant means for transport of goods, which in turn has caused a boom in data volumes exchanged at sea. Internet connectivity at sea is heavily reliant on satellites, but it suffers from high cost, low bandwidth and complex regulatory requirements. This acts as an impetus to find alternative means of connection to ease marine communication. Methodology: A literature review related to SANET, followed by an analytical and simulation model-based evaluation, along with real-life trace analysis were performed. Three routing protocols (namely, ER, RRS, and S&W) and three communication technologies (VHF, LR-WiFi and WiMax) were inspected based on three use-cases: sending small data in emergency, large data sharing route information, and very large data for insurance purpose. Findings: The evaluation shows that VHF is suitable for distant communication of small data files, whereas WiMax works better for faster transmission of large data files. The performance of the routing protocols is heavily dependent on the deployed scenarios. Originality: To the best of our knowledge, this study is the first to compare the combination of the three communication technologies and routing protocols. The study paves the path for choosing appropriate technologies and routing protocols for the deployment of SANET in maritime logistics.
urn:nbn:de:gbv:830-882.0200996; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Maritime Logistics